Analisis Peramal Kepuasan Pelajar Terhadap Proses Pelaksanaan Projek Sarjana Muda. - Mohd Tahir, Lokman; Noordin, Shahrom; Nordin, Aziz (Sains Humanika, 2011)
Projek Sarjana Muda is considered as an academic exposure that is being organized in various forms such as thesis, research-based, software and module developments and innovation project which is compulsory for final year students. PSM ãçÇìë=çéÉê åÇá consists of learning processes which embeds the important values in research methodology and ethics, cooperation, supervision and interpersonal relationship between students and their lecturers. This research mainly focuses on the reponses relating to students’ satisfaction on the implementation of PSM. It involved three vital dimensions namely lecturers’ roles, students’ roles and the PSM management committee. A total of 623 of 2007/2008 final year students were involved as respondents for this research. In addition, this research also tries to evaluate the most influential factor on students’ satisfaction and build a path analysis using the structural equation modeling approach. Finding shows that students’ satisfaction was predicted by students’ roles and interest and considered the essential element in realizing the success of PSM implementation.